Loss of antiphospholipid antibody positivity post-thrombosis in SLE. Issue 1 (6th October 2020) - Khawaja, Muznay; Magder, Laurence; Goldman, Daniel; Petri, Michelle A
Abstract : Background/Purpose: Loss of positivity of antiphospholipid antibodies has been observed in clinical practice post-thrombosis in patients with SLE with secondary antiphospholipid syndrome (APS). Our study defined the frequency of this loss and the duration before positivity recurred. Methods: In this prospective study, patients with SLE having at least two positive antiphospholipid markers prior to thrombosis and at least 1 year of follow-up after thrombosis were included. Antiphospholipid markers included lupus anticoagulant (dilute Russell viper venom test >45 s followed by mixing and confirmatory tests) and/or anticardiolipin titre (aCL IgG ≥20, aCL IgM ≥20 and/or aCL IgA ≥20). The percentage of visits with positive antiphospholipid markers after thrombosis was calculated. For patients with a negative antiphospholipid marker any time after thrombosis, survival estimates were performed to calculate the time to return of antiphospholipid positivity. Results: In APS due to SLE, complete loss of antiphospholipid positivity post-thrombosis was up to 41% for aCL IgG, 51% for IgM and 50% for IgA, but only 20% for those with lupus anticoagulant. Of those who at some point lost aCL IgG or became negative for lupus anticoagulant, the majority (60% and 76%, respectively) reacquired the antibody within 5 years. In contrast, of those who lost aCL IgM or IgA, fewer reacquired it within 5 years (37% and 17%, respectively). Conclusion: Intermittent positivity of antiphospholipid antibodies is present in APS due to SLE. These fluctuations make it difficult to decide on length of anticoagulation. Lupus anticoagulant is more likely to persist post-thrombosis.